Media Pembelajaran Matematika Berbasis Kartun untuk Menurunkan Kecemasan Siswa - Maharani, Maghfira; Supriadi, Nanang; Widiyastuti, Rany (Universitas Islam Negeri Raden Intan Lampung, 2018)
This research aims to developing a cartoon-based mathematics learning media to reduce students' anxiety. The resulting product is a cartoon-based mathematics learning media using macromedia flash software for grade VII students of SMP on social arithmetic material. This research uses 4D research and development method, proposed by Thiagarajan consisting of 4 stages: (1) define or define; (2) design or design; (3) develop or development and (4) disseminate or disseminate. Researchers use qualitative and quantitative data analysis techniques. This research uses data collection techniques which are based on a questionnaire in the form of Likert scale for student response and student anxiety. The result of the research is a cartoon-based mathematics learning media which is suitable for learning media to decrease students' anxiety. The feasibility of instructional media resulting from material experts and media experts is valid and worthy of use as a medium of learning. The students’ response to the learning media obtained in small group test is very interesting with the average score of 3.52. In the large group test obtained, the criteria of attractiveness is very interesting with an average score of 3.41. Levels of students’anxiety after the use of learning media have decreased, ie in the high anxiety category it has decreased from 41% to 0%, in the medium anxiety category it has decreased fom 35% to 24%, in the low anxiety category it has changed from 24% to 76%.